THE INFLUENCE OF DIFFERENT DOSES OF ULTRAVIOLET RAYS ON THE RESISTANCE OF PATHOGENIC MICROORGANISMS IN EXPERIMENT (IN VITRO) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Wound infection, including postoperative infection, continues to be one of the most pressing problems in surgery. The problem of microflora resistance makes it difficult to obtain positive results of purulent-surgical diseases of soft tissues. There is little research in the literature devoted to suppressing existing antibiotic resistance.